2019
DOI: 10.1021/acs.analchem.9b01347
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Femtogram-Level Plutonium Isotopes in Environmental and Forensic Samples with High-Level Uranium Using Chemical Separation and ICP-MS/MS Measurement

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 44 publications
(113 reference statements)
9
61
0
Order By: Relevance
“…Research fields and objectives. The research fields of the above references covered biology, 1-15 energy, 16 environment, 9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] food/medical, 10-12,25-27,33-40 geology, 28,41-47 material, [48][49][50][51][52][53][54][55][56][57][58][59][60] and radionulide, 4,[22][23][61][62][63][64][65][66][67][68][69][70][71] respectively. In addition to these conventional elemental analysis topics, a study on the gas phase catalytic reaction has also been reported by using the reaction cell of ICP-QMS/QMS as the in-situ reaction field.…”
Section: References Investigatedmentioning
confidence: 99%
“…Research fields and objectives. The research fields of the above references covered biology, 1-15 energy, 16 environment, 9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] food/medical, 10-12,25-27,33-40 geology, 28,41-47 material, [48][49][50][51][52][53][54][55][56][57][58][59][60] and radionulide, 4,[22][23][61][62][63][64][65][66][67][68][69][70][71] respectively. In addition to these conventional elemental analysis topics, a study on the gas phase catalytic reaction has also been reported by using the reaction cell of ICP-QMS/QMS as the in-situ reaction field.…”
Section: References Investigatedmentioning
confidence: 99%
“…Their observations are in good agreement with our findings: for similar experimental conditions (APEX Ω and O 2 in the CRC) we obtained a hydride rate in the same order of magnitude, ~0.15×10 -6 (Figure 1). Hou et al 45 also observed a significant hydride decrease with the use of the APEX Ω compared to other introduction systems. The hydride decrease with the use of the APEX Ω can be explained by the presence of a helical EPTFE fluoropolymer membrane desolvator, allowing a more efficient removal of solvent and matrix components of a sample than what the APEX-HF is capable of.…”
Section: Reduction Of the Hydride Formation Ratementioning
confidence: 93%
“…Typical hydride values without gas in the CRC and by using an APEX-HF were determined at about 25×10 -6 (Figure 1), which is in good agreement with previous studies. 34,45,58 Moreover, the N 2 gas in the APEX-HF was tested at different flow rates and, as it can be seen in figure 1, its use has not led to a hydride reduction. One parameter that influences the hydride formation rate is the molarity of the nitric acid of the analysed solution.…”
Section: Reduction Of the Hydride Formation Ratementioning
confidence: 99%
“…Pu, Am, and Cm [8][9][10][11][12][13][14][15][16][17][18][19][20]. Alternatively, ICP-MS is an attractive method for measurement of long-lived transuranic element radioisotopes, especially to measure 239 Pu and 240 Pu individually [2,4,5,[21][22][23][24][25][26][27][28][29][30]. Due to similar alpha decay energies of 239 Pu and 240 Pu, these nuclides are difficult to be discriminated in alpha spectrometry, although it is possible to resolve 239 Pu from 240 Pu in an alpha spectrum by using thin target prepared by electrodeposition [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%